ANALISIS LITERATUR: EFEKTIVITAS SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN DAERAH RAWAN BENCANA - Agnes Selan; Diana Yanni Ariswati; Saekoko, Jurni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2025)
Indonesia is one of the countries with the highest disaster vulnerability due to its geographic location at the intersection of three major tectonic plates. This condition requires a disaster mitigation system based on technology, one of which is the use of Geographic Information Systems (GIS). This study aims to evaluate the effectiveness of GIS in mapping disaster-prone areas through a literature review of 15 national and international scientific publications from 2013 to 2023. The findings show that GIS is effective in improving mapping accuracy, accelerating the identification of vulnerable zones, and supporting decision-making in disaster management. Integration with technologies such as real-time sensors, satellite imagery, IoT, and AI further enhances its role in early warning systems. However, challenges remain, including the lack of up-to-date spatial data, limited expertise, and infrastructure gaps in remote areas. Therefore, strengthening human resources and improving infrastructure are essential to optimize the implementation of GIS in disaster mitigation.